Moments that made the movies - Thomson, David, 1941- (Thames & Hudson, 2013)
Film scholar David Thomson focuses in on a series of moments-- which his readers will also experience in beautifully reproduced imagery-- from 72 films across a 100-year-plus span. Moments takes readers on an unprecedented visual tour, where the specifics of the imagery the reader is seeing are inextricably tied to the text. Thomson's moments range from a set of Eadweard Muybridge's pioneering photographs to sequences in films from the classic-- Citizen Kane, Sunset Boulevard, The Red Shoes-- to the unexpected-- The Piano Teacher, Burn After Reading. The excitement of the book's dynamic visuals will be matched only by the discussion it incites in film circles, as readers revisit their own list of memorable moments and then re-experience the films-- both those included on Thomson's list and from their own life-- as never before.--Resumé vydavatele